Android mobile application-LendNBorrow - Ten, Simin (Nanyang Technological University, 2022)
This report presents the development of an Android mobile application, LendNBorrow. LendNBorrow is designed to provide readers the ease of making book exchanging.Essentially, allowing readers to borrow/lend old books where old books can become new reads for others. LendNBorrow aims to help readers to save on average of twenty dollars to purchase a brand new printed book in bookstores. Through LendNBorrow, we are inspired to provide a platform for the communities to upload their second-hand books in Singapore. Differentiated with existing book platform, this application is designed with features that fit with book lovers, thus benefiting the readers as well as other users. This report contains four chapters. The first chapter introduces the project by providing the background information, scope and objective as well as limitations of the project. The second chapter presents the overview phase of the project, which includes the device and database of the application. Chapter three defines the implementation of the functions that are available in the application. Chapter four presents the testing phase of the application. Finally, the last chapter, chapter five contains the conclusion giving suggestions and ideas for the future development of LendNBorrow.